2021
DOI: 10.5090/jcs.16.123e1
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Outcomes of Extracorporeal Membrane Oxygenation in Children: An 11-Year Single-Center Experience in Korea

Abstract: There was an error in the article, "Outcomes of extracorporeal membrane oxygenation in children: an 11-year single-center experience in Korea [1]." The indentation in Table 4 needs to be corrected. The corrected Table 4 is as follows:We apologize for any inconvenience that it may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There is no clear definition of the timing of early EN. Some studies have suggested (36) that EN performed within 24-72 h after ICU admission is early stage. Buckvold et al ( 37) pointed out that it is safe to carry out EN within 24 to 36 h. ESPNIC recommends that EN should be performed as early as possible for full-term neonates, critically ill children and children after cardiac surgery who are hemodynamically stable with extracorporeal life support (ECLS) or dependent on drugs.…”
Section: Nutritional Support During Ecmo 41 Enteral Nutritionmentioning
confidence: 99%
“…There is no clear definition of the timing of early EN. Some studies have suggested (36) that EN performed within 24-72 h after ICU admission is early stage. Buckvold et al ( 37) pointed out that it is safe to carry out EN within 24 to 36 h. ESPNIC recommends that EN should be performed as early as possible for full-term neonates, critically ill children and children after cardiac surgery who are hemodynamically stable with extracorporeal life support (ECLS) or dependent on drugs.…”
Section: Nutritional Support During Ecmo 41 Enteral Nutritionmentioning
confidence: 99%